The circuits and filters handbook. - Chen, Wai-Kai, 1936- (CRC Press, 2009)
Upon its initial publication, The Circuits and Filters Handbook broke new ground. It quickly became the resource for comprehensive coverage of issues and practical information that can be put to immediate use. Not content to rest on his laurels, in addition to updating the second edition, editor Wai-Kai Chen divided it into tightly-focused texts that made the information easily accessible and digestible. These texts have been revised, updated, and expanded so that they continue to provide solid coverage of standard practices and enlightened perspectives on new and emerging techniques. Passive.